Ultra-efficient and stable heterogeneous iron-based Fenton nanocatalysts for degrading organic dyes at neutral pH via a chelating effect under nanoconfinement. Issue 48 (12th May 2020) - Lin, Jiayou; Chen, Sheng; Xiao, Hongyan; Zhang, Jiawen; Lan, Jianwu; Yan, Bin; Zeng, Hongbo
Abstract : An ultra-efficient and stable heterogeneous iron-based Fenton nanocatalyst has been developed for degrading organic dyes at neutral pH via a chelating effect under nanoconfinement. Abstract : An ultra-efficient and stable heterogeneous iron-based Fenton nanocatalyst has been developed for degrading organic dyes at neutral pH via a chelating effect under nanoconfinement. The catalyst demonstrates an exceptionally high degradation capacity of 2600 mg g −1 for methylene blue and rapid degradation efficiencies at neutral and basic conditions. Moreover, MPOPs are highly stable and recyclable without any obvious performance loss and iron leaching under different pH conditions.